KONSEP ISLAM WASATHIYAH PERSPEKTIF DIDIN HAFIDHUDDIN - Naufal Abdul Afif; Kholil Nawawi; Yono Yono (Universitas Pahlawan Tuanku Tambusai, 2022)
Da'wah is a spirit in Islamic teachings. Everything a Muslim does in his life must reflect Islamic values. The delivery of da'wah to the community must be with wisdom and in accordance with the example carried out by the Prophet, not making it difficult for the people by burdening the extremity and not hoping as liberals do, but with washatiyah or moderation. This study tries to find out how the Islamic concept of Washotiyyah according to Didin Hafidhuddin. This study uses a qualitative method with an interview approach to the character concerned. The results of the study prove that Islam washatiyah is an important thing to be understood and practiced by Muslims today, because of the many deviations and confusion in society. Keywords : Didin Hafidhuddin, Islam, Islam Washotiyyah